MEDIASI VARIABEL KINERJA KARYAWAN PADA PENGARUH PENGEMBANGAN KARIR DAN LINGKUNGAN KERJA FISIK TERHADAP KEPUASAN KERJA PADA PO. PANCA SARI TOUR DAN TRAVEL KANTOR MATARAM - I GUSTI AGUNG DIDIT EKA PERMADI; NI WAYAN NADIA SARI; I DEWA GEDE SUARTHA (GANEC SWARA, 2024)
The purpose of this research is to analyze the significant influence of career development on employee job satisfaction, the significant influence of the physical work environment on employee job satisfaction, the significant influence of career development on employee performance, the significant influence of the physical work environment on employee performance, and the significant influence of job satisfaction on employee performance P.O. Panca Sari Tour and Travel Mataram Office. This research is associative or causal research. The data collection method used in this research is the census method. The data analysis technique used is path analysis. The conclusion obtained is that career development and the physical work environment have a significant effect on job satisfaction so that the job satisfaction obtained will influence the performance of PO employees. Panca Sari Tour and Travel Mataram Office. Suggestions that can be given based on the conclusions obtained from the research results are PO. Panca Sari Tour and Travel Mataram Office also needs to pay attention and even add work equipment facilities for employees. This is to support increased job satisfaction and performance of the employees themselves